K+ preference at the NaK channel entrance revealed by fluorescence lifetime and anisotropy analysis of site-specifically incorporated (7-hydroxycoumarin-4-yl)ethylglycine. Issue 88 (18th September 2015) - Liu, Sanling; Lv, Pei; Li, Dong; Guo, Xiaoqi; Zhang, Bo; Yu, Mu; Li, Dandan; Xiong, Ying; Zhang, Longhua; Tian, Changlin
Abstract : Fluorescence lifetime and time-resolved anisotropy measurements were used for characterizing the ion preference of the NaK channel. Abstract : The fluorescent unnatural amino acid, (7-hydroxycoumarin-4-yl)ethylglycine (HC), was site-specifically incorporated at the Phe69 site, close to the entrance of the selectivity filter of the NaK channel. Decreased fluorescence lifetime and elevated time-resolved anisotropy of NaK-F69HC in buffers with high K + /Na + molar ratios indicated the K + preference at the entrance of the NaK channel, consistent with previous crystal structure results of the NaK channel.